Michelangelo Antonioni and Atom Egoyan: Contaminating identities - Baso, Giulia (Journal of Italian Cinema & Media Studies, 2016)
Abstract This article aims to bring together two major directors, Michelangelo Antonioni and Atom Egoyan, in a way that sheds new light upon their oeuvres. It is inspired by an unrealized venture, a screen adaptation that the two auteurs were supposed to film together in the late 1990s, provisionally entitled Just to Be Together. Focusing on what came before this suspended artistic collaboration, the present study proposes a comparative reading of Professione: Reporter/The Passenger and Next of Kin, developed through the theoretical work of Rosi Braidotti and Richard Dyer. It attempts to rethink the ‘auteur of modernist alienation’ from the perspective of contemporary theoretical frameworks, and beyond the specific context of Italian film culture. At the same time, it argues for a repositioning of Egoyan’s debut feature film in a non-strictly diasporic context, entering debates around accented and transnational models in film studies.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qaWNtcy40LjEuNTFfMQ